Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1039/c1cc12806j
|View full text |Cite
|
Sign up to set email alerts
|

Ordered mesoporous carbon catalyst for dehydrogenation of propane to propylene

Abstract: Metal-free ordered mesoporous carbons were demonstrated to be robust catalysts for direct dehydrogenation of propane to propylene, in the absence of any auxiliary steam, exhibiting high activity and selectivity, as well as long catalytic stability, in comparison with nanostructured carbons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 23 publications
2
82
0
Order By: Relevance
“…The detection of dopamine in the presence of ascorbic acid was then obtained with a low detection limit. It has also found that the oxygen functional groups play an important role in the catalytic activity for the dehydrogenation of propane to propylene [34].…”
Section: Influence Of the Oxygen-containing Functional Groups And Thementioning
confidence: 99%
“…The detection of dopamine in the presence of ascorbic acid was then obtained with a low detection limit. It has also found that the oxygen functional groups play an important role in the catalytic activity for the dehydrogenation of propane to propylene [34].…”
Section: Influence Of the Oxygen-containing Functional Groups And Thementioning
confidence: 99%
“…18 In consideration of the hydrophilic properties of the sulphonic and carboxyl groups, these adsorbed groups on the surface of the adsorbent through hydrophobic effects are more outward to the aqueous solution due to the electrostatic repulsion between the adsorbed PFOS/ PFOA. Besides, a new insight into the sorption mechanism of ionizable compounds on carbon nanotubes was reported, 30 which revealed that ionizable compounds could interact with adsorbents using the charge-assisted hydrogen bond. The arrangements of the possible charge-assisted hydrogen bond for PFOA on adsorbents are similar to those noted through the hydrophobic effect.…”
Section: Effect Of C-f Chain Lengthmentioning
confidence: 99%
“…Carbon materials with a high surface area and large pore volume have found an increasing number of applications in catalysis, adsorption, separation or electrochemistry [6][7][8][9][10][11][12][13][14]. Very promising results were collected over metal-free carbon nanomaterials (e.g.…”
mentioning
confidence: 99%